A thorium-doped catalyst for the high temperature shift reaction - Rangel Costa, João Luı́s (2002)
The reforming of natural gas feedstock in the presence of steam is the main industrial route to produce high purity hydrogen. However, this process also produces carbon oxides which can poison most hydrogenation catalysts as well as ammonia catalysts. In industrial processes, these compounds are often removed from the gaseous stream by the water gas shift reaction (WGSR), which is performed in two steps due to thermodynamics and kinetics considerations. A chromium and copper-doped hematite has been recently proposed as an industrial catalyst in the high temperature shift (HTS). This solid shows a stable performance but the search for non-toxic systems is much needed due to environmental restrictions related to chromium compounds. In this work, the use of thorium instead of chromium in iron- and copper-based catalysts for the HTS reaction was investigated. Catalysts were prepared in the active form (magnetite) in order to save energy, characterized by several techniques and then evaluated in operational conditions close to the industrial ones. It was found that thorium can replace chromium in these catalysts leading to better catalytic properties as compared to chromium. The catalyst has the advantage of being less toxic and can be prepared in the active phase.